Pharmacological and psychological approaches to insomnia treatment in cardiac patients: a narrative literature review - Stapel, Britta; Alvarenga, Marlies E.; Kahl, Kai G. (Frontiers in Psychiatry, 2025)
Sleep disorders are highly prevalent in the general population and are considered a major public health issue. Insomnia constitutes the most frequent sleep disorder in healthy individuals and has been shown to be even more frequent in patients with physical illnesses including cardiovascular diseases. Inadequate sleep quality and short sleep duration, independent of underlying causes, have been linked to the development and progression of cardiometabolic disorders. Additionally, insomnia has been found to be associated with adverse outcome measures, including daytime sleepiness, fatigue, decreased self-reported physical functioning, lower exercise capacity, poor health related quality of life, depressive symptoms, higher rates of hospitalization and increased mortality in patients with cardiovascular diseases. Against this background, comparatively little information is available in the literature regarding the treatment of chronic insomnia in cardiac patient populations. While guidelines for the general population suggest cognitive behavioral therapy for insomnia as a first-line treatment option and preliminary evidence suggests this treatment to be beneficial in cardiac patients with insomnia symptoms, it is often limited by availability and possibly the clinician’s poor understanding of sleep issues in cardiac patients. Therefore, pharmacologic treatment remains an important option indicated by the high number of hypnotic drug prescriptions in the general population and in patients with cardiovascular disorders. In this narrative review of the literature, we summarize treatment options for chronic insomnia based on clinical guidelines for the general population and highlight necessary considerations for the treatment of patients with cardiovascular diseases.